Composite of polylactic acid/tungsten oxide/amino-functionalized carbon quantum dots (PLA/WO3/N-CQDs) fibers for oil/water separation and methylene blue decolorization - NUGRAHA, MUHAMMAD WAHYU (2021)
Oil/water separation remains a significant field for resolving the problem of industrial oily wastewater or other oil/water pollution. At least 706 million gallons of oil spills are discharged into the oceans each year. In recent years, the leading oil/water separation materials have all been metallic meshes and membranes. However, these materials have several drawbacks, including high material costs, poor resistance to some chemicals, and the fact that they can only be used for a limited number of pollutants. In contrast, porous fiber has shown promising potential for oil/water separation. Its low cost, simple setup, high efficiency, and high reusability are the main advantages to be utilized as oil/water separation material. The porous polylactic acid fiber was chosen for this present work due to its high mechanical strength, non-toxicity, and hydrophobic properties, as well as its eco-friendliness and derived from renewable resources. However, to improve the effectiveness of porous fibers, it is essential to modify its properties to achieve improved properties and ultimately improve the porous fiber performance. In that regard, tungsten oxide/ amino-functionalized carbon quantum dots (WO3/N-CQDs) were introduced as nanofillers to enhance the PLA fibers morphologies. The composite was consists of WO3, sugarcane bagasse N-CQDs, and PLA fiber which prepared by precipitation method, hydrothermal method, and electrospinning method, respectively. Preliminary studies regarding the performance of WO3/N-CQDs were also systematically conducted to examine the best composite further to be incorporated as nanofillers in electro spun porous PLA fibers. It is shown that WO3/N-CQDs alters the surface morphology, wetting behavior, and crystallinity of pristine PLA fiber. PLA/WO3/N-CQDs composite fibers show significantly enhanced hydrophobicity while maintaining surface superoleophobicity.